Women and migration - Antman, Francisca M. (Bonn, 2018)
"While scholars have long studied the economics of migration, increasing waves of international and regional migration around the world have placed greater focus on the varied impacts of migration in recent years. Critical to this line of research is an examination of the important role that women play in both sending and destination areas. This chapter addresses various aspects of the relationship between women and migration, including key ways in which non-migrant women are affected by migration, as well as how female migrants affect families and labor markets in both source and destination communities. Selection factors and determinants of female migration, as well as the gendered impacts of migrant networks, are also discussed."